AN OVERVIEW OF ANIMAL FOSTER HOMES IN BRAZIL - Taraciuk, Aline Chmilouski; Leite, Luana Oliveira; Polo, Gina; Garcia, Rita de Cassia Maria (Archives of Veterinary Science, 2020)
Animal foster homes (AFHs) provide shelter for abandoned animals and are an essential part of street population management programs. An online survey was conducted in Brazil with questions about general aspects of AFHs. A total of 150 caregivers responded, most were female (n=140; 93.3%) with a mean age of 35.4 years. AFHs in most cases conduct vaccination (n=103; 68.3%), treatment for internal parasites (n=142; 94.7%), external parasites (n=138; 92.0%) and neutering (n=113; 75.3%) to animals in their care. The principal problem for AFHs is finding adopters (n=122; 81.3%) and indeed most caregivers adopted some of the animals under their care (n=129; 86.0%). Although most AFHs reported having no limit on housing time (n=61; 40.7%), there were significant differences between short-term (< 3 months) and long term (>24 months) housing. Long-term AFHs sheltered to more than 20 animals (P<0.05), frequently from the streets (P<0.05). Short-term AFHs offered shelter to fewer than six animals (P<0.05), and generally housed old (P<0.05), chronically ill (P<0.05), amputees (P<0.05), deaf or blind animals (P<0.05) – often at the request of rescue groups (P<0.05). Sheltering fewer (<6) animals guaranteed greater adoptability in a shorter timeframe, thus avoiding kennel stress, overcrowding and potentially reducing the risk of disease outbreaks.